Technology foresight of the Internet Booking Engine Technology through Scenario Building - Arcilla, Denry L. (University of the Philippines Diliman, 2010)
This project study attempts to establish the significance of the Internet Booking Engine (IBE) technology to the firm, Sabre Holdings, and to their valued clients. In line with the established objectives, the project encourages the firm to continuously develop a superb application as it helps clients to become more profitable. Having this application lets customers of an Airline firm to book a flight easily. This project study looks forward to determining the future trends and upcoming features of the Internet Booking Engine (IBE) technology. Through Scenario Building, the goal of determining the uncertain future of the application might prevail. Scenario Building offers to demonstrate more than anything else but lifelong fascination with images of the future. The interest of identifying and analyzing images of the future leads naturally to the interest of imagining, composing, building and visualizing them. Taking the long-term analysis of the internet Booking Engine (IBE) technology, Scenario Building helps in finding out how this future trend in the application will bring a significant impact to the firm. As the world's leading provider of high performance solutions for Airlines and airports, Scenario Building contributes to address the plausible future by keeping them ahead of the competition. In view of the impacts of specific uncertainties, active engagement with key stakeholders plays a crucial task in strategy and planning. In this project study, Scenario Building was utilized to better envision the future of the Internet Booking Engine (IBE) technology, A series of conversations with key stakeholders were in placed and a few questions with the affiliated members of the software development team were asked in shaping the plausible future. Having all these results of Scenario Building implemented in the Internet Booking Engine (IBE) technology, Sabre Holdings will be at the prime spot in the Airline industry. These are first-rate packages for the clients as they try to find the same features and functionalities to their customers.